The capital structure and governance of a mortgage securitization utility - Patricia C. Mosser; Joseph Tracy; Joshua Wright (Federal Reserve Bank of New York, 2013)
We explore the capital structure and governance of a mortgage-insuring securitization utility operating with government reinsurance for systemic or 'tail' risk. The structure we propose for the replacement of the GSEs focuses on aligning incentives for appropriate pricing and transfer of mortgage risks across the private sector and between the private sector and the government. We present the justification and mechanics of a vintage-based capital structure, and assess the components of the mortgage guarantee fee, whose size we find is most sensitive to the required capital ratio and the expected return on that capital. We discuss the implications of selling off some of the utility's mortgage credit risk to the capital markets and how the informational value of such transactions may vary with the level of risk transfer. Finally, we explore how mutualization could address incentive misalignments arising out of securitization and government insurance, as well as how the governance structure for such a financial market utility could be designed.
Keywords: E02; G01; G21; G28; G32; 330; GSE; MBS; mortgage finance; cooperatives; financial market utility